An integrated Hardware/Software Verification and Validation methodology for Signal Processing Systems - Venugopal Manokar; Nanda Manju; Anand G.; Chandana Voora Hari (ITM Web of Conferences, 2022)
The testing and validation services team assesses project deliverables at various stages of development using innovative and effective verification and validation, to ensure that the deliverables are compliance with the customer specifications and requirements. Whenever new products and devices are released, completely integrated verification and validation services are delivered to accurate and complete records usability, performance, and quality assurance services. Throughout the product development and testing process, the testing and validation services team employs verification and validation techniques. Code reviews, walk through, inspections, desk-checking, and code execution are all examples of verification and validation techniques. Services for verification and validation are used to assess whether or not the software or application provided complies with the requirements and serves the intended purpose. A procedure used to ensure that the software created is of good quality and consistently operates as expected is independent testing and validation services. Unit testing (also known as “White Box Testing”), hardware-software integration testing (HSIT), and system testing are the three primary independent verification and validation approaches (Black Box Testing). The teams responsible for the verification and validation services actively participate in each stage of the project and design the services according to the project’s needs (e.g., prototype, spiral, iterative, V Model, and Agile). Our expertise in the embedded domain, tried-and-true verification and validation techniques, and a thorough methodology provide a quick turnaround and excellent results for the targeted solution. Independent Verification and validation services covering